The Effect of Consumer Electronic Behavior on Improving the Competitive Advantage: An Applied Study on the Tourism Services Sector in Jordan - Alqurashi, Daher (The Arab Journal of Administration, 2021)
The study aimed to identify the impact of electronic consumer behavior in its dimensions (electronic marketing, electronic purchase, direct electronic payment, indirect electronic payment(,on improve the competitive advantage with its components (consumer confidence in the product, achieving consumer safety, stability of product quality, time), In the tourism services sector in Jordan, And show the impact of each dimension and one of those dimensions and elements, The study used the descriptive analytical method, and a sophisticated questionnaire was designed to suit the objectives of the study, (478) questionnaires were distributed to a convenes sample of those who meet the conditions of the sample, (388) questionnaires were retrieved, all of which were subjected to statistical analysis, at a rate of (81%) of the total distributed questionnaires. It was statistically treated according to the appropriate statistical methods, the study came out with a set of results, the most important: there is a statistically significant effect on the electronic consumer behavior of improving the competitive advantage in the tourism services sector in Jordan, The average for all axes of electronic consumer behavior has reached (3.77) at a high level and came first, And that the average for all axes of electronic consumer behavior has reached (3.77) at a high level, and the study also showed that the e-marketing dimension came in first place with average (4.01), The study presented several recommendations, including: the need to increase the interest of tourism companies in the behavior of the electronic consumer behavior better than it is currently, and to develop applications for promotion and private websites in the tourism sector, to increase electronic cultural awareness because of its great importance to electronic consumer behavior.